2006
DOI: 10.1007/s10995-006-0107-x
|View full text |Cite
|
Sign up to set email alerts
|

The National Summit on Preconception Care: A Summary of Concepts and Recommendations

Abstract: The Centers for Disease Control and Prevention (CDC) and 35 partner organizations have engaged in developing an agenda for Preconception Health. A summit was held in June 2005 to discuss the current state of knowledge regarding preconception care and convene a select panel to develop recommendations and action steps for improving the health of women, children, and families through advances in clinical care, public health, and community action. A Select Panel on Preconception Care, convened by CDC, deliberated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 15 publications
2
61
0
1
Order By: Relevance
“…Because the construction of preconception care in Chinese policies centers around marriage, the inclusion of men in preconception care can be traced back to the 1970s, as compared to the relatively new inclusion of men in the U.S. setting (3). Further, this study also found that the preconception health and care policy language of the Chinese government, both at national and provincial levels, has mainly a biomedicine focus, similar to the dominant preconception health and care policy languages in international settings (6). However, the Chinese preconception care policies also contain a nonbiomedical message that is constructed around menstrual care.…”
Section: Discussionsupporting
confidence: 55%
“…Because the construction of preconception care in Chinese policies centers around marriage, the inclusion of men in preconception care can be traced back to the 1970s, as compared to the relatively new inclusion of men in the U.S. setting (3). Further, this study also found that the preconception health and care policy language of the Chinese government, both at national and provincial levels, has mainly a biomedicine focus, similar to the dominant preconception health and care policy languages in international settings (6). However, the Chinese preconception care policies also contain a nonbiomedical message that is constructed around menstrual care.…”
Section: Discussionsupporting
confidence: 55%
“…The Centers for Disease Control and Prevention (CDC) and 35 partner organizations convened a national summit on preconception care in 2005, and released policy recommendations in 2006 (Posner et al, 2006). Identification of carrier status for genetic conditions (including CF) that could be assessed prior to pregnancy is advocated in the recently released policies (Atrash et al, 2006;Posner et al, 2006;Shapira and Dolan, 2006). In addition, updated 2005 ACOG recommendations for CFCT placed more emphasis on offering CFCT to all couples, rather than focusing primarily on couples planning pregnancy or during pregnancy (Committee on Genetics ACOG, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Once they are detected, most of these risk factors can be managed or treated before conception to prevent or limit fetal exposure [8]. Pre-conception care is defined as ‘a set of interventions that aim to identify and modify biomedical, behavioural, and social risks to a woman's health or pregnancy outcome through prevention and management, emphasizing those factors that must be acted on before conception or early in pregnancy to have maximal impact' [9]. …”
Section: Introductionmentioning
confidence: 99%